Core diameter and numerical aperture dependences on the performance of fiber-optic multimode interference sensing. (1st January 2023) - Wang, Kun; Mizuno, Yosuke; Su, Xingyu; Dong, Xingchen; Kurz, Wolfgang; Fink, Maximilian; Lee, Heeyoung; Jakobi, Martin; Koch, Alexander W.
Abstract: Modal interference in a multimode fiber (MMF) has been utilized to develop simple sensors for various physical parameters. Herein, first, we investigate the dependences of the core diameter and the numerical aperture (NA) of the MMF on the performance of multimode-interference-based strain and temperature sensing. We find that a larger core diameter leads to higher temperature sensitivity but lower strain sensitivity (absolute value) and that higher NA does not influence the temperature sensitivity but results in higher strain sensitivity (absolute value). Subsequently, using the obtained low strain sensitivity, we demonstrate strain-insensitive temperature sensing with a sensitivity of approximately 6.1 pm °C −1 .